Control of power-augmenting lower extremity exoskeleton while walking with heavy payload. (19th February 2019) - Choi, Byunghun; Seo, Changhoon; Lee, Sanghoon; Kim, Byungun
This article presents a design and control framework for a prototype of lower extremity exoskeleton to enhance the human strength during locomotion. The hybrid control strategy is practically applied according to the two gait phases, that is, stance and swing. The weight shift method based on human's weight shift information was proposed and implemented to acquire the detection of gait phase. In the stance phase, a stiff virtual wall method is applied to support the entire weight of the exoskeleton while carrying a heavy payload. Direct feedback and feed-forward torque control are used to reduce mechanical impedance in the swing phase. In experiments, to verify the performance of the proposed control strategy, a human subject wearing the prototype of power-augmenting lower extremity exoskeleton was able to walk with a 50-kg (110-lb) payload at a maximum speed of 1.67 m/s (6 km/h). Satisfactory results were obtained with regard to walking experiments with the heavy payload.